LEADERSHIP IN SPORT GOVERNANCE - O'Boyle, Ian.; McLeod, Joshua; Takos, Nick. ([S.l.] : ROUTLEDGE, 2024)
This is a concise introduction to leadership and governance theory and how they are applied in sport. Presenting a series of case studies from around the world, the book offers a detailed guide to best practice in the leadership of sport boards and organisations. Drawing on cutting-edge research, the book sets out the core concepts and principles of good leadership and good governance, explaining their importance in an era in which sport organisations have become increasingly bound by legal frameworks and subject to greater calls for accountability from wider society. The book analyses the key issues related to leadership in sport governance, including leadership styles with a focus on authentic leadership; intra-group dynamics; managing conflict and trust; leading in multi-layered networks; strategic leadership; and diversity, equity, and inclusion (DEI); and it considers the differing requirements of sport leadership in different geographical locations, under varying challenges and pressures. Full of illuminating cases, data and examples, this is an invaluable reading for any course in sport business and management and a useful primer for any sport business professional looking to improve their professional knowledge.
Keywords: Sports administration; Leadership; BUSINESS & ECONOMICS / Leadership